Liberalisasi pendidikan dan cabarannya dalam kontek pendidikan Islam di Malaysia - Hashim, Rosnani (Yayasan Takmir, 2007)
This article discusses the impact globalization, in particular the liberal economy, on education. It elaborates how the liberalized economy requires a new kind of worker who needs a different set of skills, especially knowledge of the information and communication technologies (ICT). Due to this, there is a greater demand for higher education which could not all be met by the government, thereby resulting in the privatization of education. Liberalization also brings with it internationalization which means the hegemony of the English language and also accountability through international comparison in education, thereby scrutinizing local education system to international standards. The article subsequently analyses the impact of this new development such as the dehumanization, the technologization, the Englishnization and the possible resecularization of education on Islamic and Muslim education. It concludes with an examination of the role of zakat institution for financing for Muslim educational institutions and suggests changes in Islamic and Muslim education to meet these new challenges.